The histone methyltransferase SDG8 mediates the epigenetic modification of light and carbon responsive genes in plants - Li, Ying (2015)
Background: Histone methylation modifies the epigenetic state of target genes to regulate gene expression in the context of developmental and environmental changes. Previously, we used a positive genetic screen to identify an Arabidopsis mutant, cli186, which was impaired in carbon and light signaling. Here, we report a deletion of the Arabidopsis histone methyltransferase SDG8 in this mutant (renamed sdg8-5), which provides a unique opportunity to study the global function of a specific histone methyltransferase within a multicellular organism. Results: To assess the specific role of SDG8, we examine how the global histone methylation patterns and transcriptome were altered in the sdg8-5 deletion mutant compared to wild type, within the context of transient light and carbon treatments. Our results reveal that the sdg8 deletion is associated with a significant reduction of H3K36me3, preferentially towards the 3′ end of the gene body, accompanied by a reduction in gene expression. We uncover 728 direct targets of SDG8 that have altered methylation in the sdg8-5 mutant and are also bound by SDG8. As a group, this set of SDG8 targets is enriched in specific biological processes including defense, photosynthesis, nutrient metabolism and energy metabolism. Importantly, 64% of these SDG8 targets are responsive to light and/or carbon signals. Conclusions: The histone methyltransferase SDG8 functions to regulate the H3K36 methylation of histones associated with gene bodies in Arabidopsis. The H3K36me3 mark in turn is associated with high-level expression of a specific set of light and/or carbon responsive genes involved in photosynthesis, metabolism and energy production.